A Comparison of Estimated and Reported Historical Cost/Constant Dollar Data. - Walther, Larry M. (The Accounting Review, 1982)
Abstract ABSTRACT: SFAS 33 requires certain companies to present historical cost/constant dollar data. The disclosures provide a data base against which to compare results achieved by the Davidson-Weil historical cost/constant dollar data estimation model. This Note reports the result of research that was conducted to measure the degree of variation between surrogate historical cost/constant dollar data generated by the Davidson-Weil model and historical cost/constant dollar data presented by 459 companies. The Davidson-Well model estimate of historical cost/constant dollar cost of goods sold was in excess of reported amounts by an average of .54 percent, the model estimate of historical cost/constant dollar depreciation expense exceeded reported amounts by an average of 13.73 percent, and the model estimate of the purchasing power gain/loss exceeded reported amounts by an average of 68.3 percent.